Efficacy of transarterial chemoembolization monotherapy or combination conversion therapy in unresectable hepatocellular carcinoma: A systematic review and meta-analysis - Li, Weiwei; Pei, Yinxuan; Wang, Zixiang; Liu, Jinlong (Frontiers in Oncology, 2022)
Background: Hepatocellular carcinoma (HCC) is a highly malignant disease with poor prognosis, and most cases were already considered unresectable at the time of presentation. Conversion therapy, as an emerging treatment, designed to provide patients with initially unresectable HCC (uHCC) the opportunity to undergo radical resection. At present, conversion therapy for patients with uHCC remains controversial. Transarterial chemoembolization (TACE) is currently the most widely selected treatment for uHCC, but its efficacy as conversion therapy remains controversial. Method: We compared and evaluated the conversion rate and tumor response of TACE monotherapy or combination therapy. Meanwhile, postoperative complications and overall survival in uHCC patients who underwent conversion therapy were also analyzed. Results: A total of 18 studies were included in this meta-analysis. The conversion rate for triple therapy [TACE in combination with tyrosine kinase inhibitor (TKI) and immune checkpoint inhibitor (ICI)] was 42% [95% confidence interval (CI): 0.29-0.56], higher than any other group [TACE monotherapy: 10% (95% CI: 0.08-0.12), bigeminy therapy: 19% (95%CI: 0.06-0.36)]. Meanwhile, triple therapy yielded a better tumor response than TACE monotherapy or bigeminy therapy. Among the patients with successful surgical resection after conversion therapy, the pooled postoperative OS rates at 1, 2, and 5 year(s) were 90% (95% CI, 0.81–0.97), 58% (95% CI, 0.42–0.73), and 42% (95% CI, 0.26–0.60), and the major postoperative complications were biliary leakage (7%; 95% CI, 0.03–0.12) and liver failure (3%; 95% CI, 0.00–0.07). Conclusion: TACE conversion therapies showed good conversion rates, especially the triple therapy of TACE in combination with TKI and ICI. Surgical resection after successful conversion therapy could maximize the outcome of patients with uHCC.